Sarcoidosis Treatment with Antifungal Medication: A Follow-Up - Terčelj, Marjeta; Salobir, Barbara; Zupancic, Mirjana; Rylander, Ragnar (Pulmonary Medicine, 2014)
Introduction. The aim of the study was to compare treatment of sarcoidosis with antifungal or corticosteroid medication. Methods. In patients with sarcoidosis antifungal medication (n=29), corticosteroids (n=21) or a combination (n=27) was given. Nine patients allotted to antifungal medication were later given corticosteroids because of the lack of regression of the disease. X-ray scores for the severity of granuloma infiltration were determined. Chitotriosidase and angiotensin converting enzyme were determined. The time in months till remission was observed as well as the number of recurrences.